Subfailure Overstretch Injury Leads to Reversible Functional Impairment and Purinergic P2X7 Receptor Activation in Intact Vascular Tissue - Luo, Weifeng; Guth, Christy M.; Jolayemi, Olukemi; Duvall, Craig L.; Brophy, Colleen Marie; Cheung-Flynn, Joyce (Frontiers in Bioengineering and Biotechnology, 2016)
Vascular stretch injury is associated with blunt trauma, vascular surgical procedures, and harvest of human saphenous vein for use in vascular bypass grafting. A model of subfailure overstretch in rat abdominal aorta was developed to characterize surgical vascular stretch injury. Longitudinal stretch of rat aorta was characterized ex vivo. Stretch to the haptic endpoint, where the tissues would no longer lengthen, occurred at twice the resting length. The stress produced at this length was greater than physiologic mechanical forces but well below the level of mechanical disruption. Functional responses were determined in a muscle bath, and this subfailure overstretch injury led to impaired smooth muscle function that was partially reversed by treatment with purinergic receptor (P2X7R) antagonists. These data suggest that vasomotor dysfunction caused by subfailure overstretch injury may be due to the activation of P2X7R. These studies have implications for our understanding of mechanical stretch injury of blood vessels and offer novel therapeutic opportunities.